Penyelesaian :
→ f(x) = x × x + x² ÷ x!!
→ f(6) = 6 × 6 + ( 6 × 6 ) ÷ 6!!
→ f(6) = 36 + ( 6 × 6 ) ÷ 6!!
→ f(6) = 36 + 36 ÷ ( 6 × 4 × 2 )
→ f(6) = 36 + 36 ÷ ( 24 × 2 )
→ f(6) = 36 + ( 36 ÷ 48 )
→ f(6) = 36 + 0,75
→ f(6) = 36,75
I Hope This Help-!
f(x) = x × x + x² ÷ x!!
f(6) = 6 × 6 + 6² ÷ (6 × 4 × 2)
= 6 × 6 + 6(6) ÷ 48
= 36 + 36 ÷ 48
=
× 4
= 144 + 3
= 147
Atau
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
JAWABAN
Penyelesaian :
→ f(x) = x × x + x² ÷ x!!
→ f(6) = 6 × 6 + ( 6 × 6 ) ÷ 6!!
→ f(6) = 36 + ( 6 × 6 ) ÷ 6!!
→ f(6) = 36 + 36 ÷ ( 6 × 4 × 2 )
→ f(6) = 36 + 36 ÷ ( 24 × 2 )
→ f(6) = 36 + ( 36 ÷ 48 )
→ f(6) = 36 + 0,75
→ f(6) = 36,75
I Hope This Help-!
f(x) = x × x + x² ÷ x!!
f(6) = 6 × 6 + 6² ÷ (6 × 4 × 2)
= 6 × 6 + 6(6) ÷ 48
= 36 + 36 ÷ 48
=![\tt 36+\frac{3}{4} \tt 36+\frac{3}{4}](https://tex.z-dn.net/?f=%5Ctt%2036%2B%5Cfrac%7B3%7D%7B4%7D)
× 4
= 144 + 3
= 147
Atau
=![\tt \frac{147}{4} \tt \frac{147}{4}](https://tex.z-dn.net/?f=%5Ctt%20%5Cfrac%7B147%7D%7B4%7D)